The value of AI in the Diagnosis, Treatment, and Prognosis of Malignant Lung Cancer - Wang, Yue; Cai, Haihua; Pu, Yongzhu; Li, Jindan; Yang, Fake; Yang, Conghui; Chen, Long; Hu, Zhanli (Frontiers in Radiology, 2022)
Malignant tumors is a serious public health threat. Among them, lung cancer, which has the highest fatality rate globally, has significantly endangered human health. With the development of artificial intelligence (AI) and its integration with medicine, AI research in malignant lung tumors has become critical. This article reviews the value of CAD, computer neural network deep learning, radiomics, molecular biomarkers, and digital pathology for the diagnosis, treatment, and prognosis of malignant lung tumors.